Factor Analysis of the e-Marketplace Selection Model From a Seller Perspective - Eko Purwanto,; Farahwahida binti Mohd,; Zalizah Awang Long,; Singgih Purnomo, (Journal of Computing Technologies and Creative Content, 2025)
Each e-marketplace has different characteristics, so in choosing the e-marketplace that the seller will use, he must consider many factors. Based on the research results it is known that (1) the factors that are formed based on factor analysis are as many as 2 factors, namely the Product Quality Service Factor and the Quality and System Factor. This study uses a factor analysis model to carry out analysis using data analysis. The research data used were the results of a questionnaire survey. The questionnaire was made online by e-commerce sellers in Surakarta, Indonesia. The questionnaire is a Likert scale comprising statements representing the attitude of agreeing or disagreeing with the statements specified in the questionnaire. The topic of this research is the e-marketplace selection model from the seller's perspective. The results of the analysis with SPSS show that KMO = 0.908 and spherical Bartlett = 0.000, the contribution levels of the two common factor variants extracted are: F1 = 49.525%, F2 = 20.321%, the data results above show that seller's trust in e-marketplaces and support External is the reason for sellers to choose e-marketplaces to market their products. The Factor Analysis Model for selecting e-marketplaces can add references to the theoretical basis.